DEMOCRACY AND HUMAN RIGHTS AND THEIR ROLE IN ACHIEVING SUSTAINABLE DEVELOPMENT - Abdul Mutaleb Al-Bakaa, Muhamad (ALBAHITH ALALAMI, 2022)
The study of the concepts of "democracy" and "human rights" and their impact on development, has taken a prominent place in the context of general political and cultural concerns, or in specialized studies even though researchers and scholars do not agree on defining the concepts: Democracy, Human Rights, Development or deriving a global definition hindering them, and that because of the importance of this topic, which proceeds from a number of considerations standing in the forefront, of which: First: What the world witnesses today in the first decade of this century of consecration of the unipolar theory, trying to give its concepts and perceptions through the law ((excessive force)) to the power of international law, and The international legitimacy that has not escaped from being harnessed into serving the strategy of this pole and the reconciliation of vitality. Second: The suffering of two-thirds of the human population, which was termed as "third world" or underdeveloped countries, from the repugnant problems of colonial domination and its effects, which were characterized by retardation, or the lack of development to a minimum, does not stop at the borders of that world, because they have become a global problem, and the international community is the one to blame, especially in an era when the interests of this vast global village were intertwined. The study of human development and the impact of democracy and human rights in it, is supposed to be an objective study, that is to say, we must take into account a number of factors and indicators that allow the possibility of defining the outlines of development and planning in the country where it takes a method and a means to promote its economy. Development plans are not prepared templates, they are ready in advance and can be transferred from country to country, applying them under the same conditions as they were before, because one of the first conditions required by development plans is (realism).